First-principles calculations to investigate the interfacial energy and electronic properties of Mg/AlN interface. (August 2022) - Yang, Tianxing; Chen, Xiaohong; Li, Wei; Han, Xiujun; Liu, Ping
Abstract: First-principles calculations were performed to study the interfacial stability of Mg/AlN interface and the heterogeneous nucleation ability of AlN particles in Mg melts. The 7-layer Mg(0001) and 11-layer AlN(0001) are thick enough to show bulk-like interior properties. And the N-terminated and Al-terminated AlN(0001) were employed to construct six interfacial models. With the largest Wad and smallest interfacial distance, the TL-site interface with N-terminated AlN(0001) is the most stable. The bond at TL-site interface with N-terminated AlN(0001) is ionic with strong covalent, while it is metallic and weak covalent for the Al-terminated SL-site interface. And the best adsorption position of Mg atoms is the N-terminated AlN(0001) surface's TL site. Highlights: The Mg(0001)/AlN(0001) interfaces with six different stackings were studied by First principle method. The N-terminated TL-stacking interface has the largest work of adhesion among the six models. The N-terminated FL-stacking interface is unstable. The interfacial bonding of N-terminated-TL stacking interface is ionic with strong covalent.